Layered MWW zeolite-supported Rh catalysts for the hydrodeoxygenation of lignin model compounds - Yoon, Ji Sun; Lee, Taehee; Choi, Jae-Wook; Suh, Dong Jin; Lee, Kangtaek; Ha, Jeong-Myeong; Choi, Jungkyu (ELSEVIER, 2017)
The improved catalytic activity of Rh nanoparticles deposited on the swollen and pillared zeolites was observed in the hydrodeoxygenation (HDO) reactions of 1,3,5-trimethoxybenzene (1,3,5-TMB), a bulky lignin model compound, and guaiacol, one of the most frequently used lignin model compounds. As the high dispersion of metal nanoparticles increases HDO activity, the swelling/calcination and pillaring of crystalline MCM-22 zeolites increased the dispersion of Rh metal nanoparticles on the external surface area, and thus the corresponding HDO activity with respect to 1,3,5-TMB. On the contrary, although the mesopores in the amorphous MCM-41 and silica-alumina aerogel (SAA) supports accommodated higher Rh dispersion, overall, the resulting catalysts suffered from mass transfer limitation, and thus showed poor HDO reaction activity for 1,3,5-TMB. Finally, the Rh nanoparticles supported on the pillared zeolite showed the highest HDO activity for guaiacol, mainly due to the higher Rh dispersion and acid sites on the external surface among the zeolite-supported Rh catalysts. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: MOLECULAR-SIEVE; ISOMERIZATION; CONDENSATION; BEHAVIOR; ALKYLATION; MONOMERS; METHANOL; CRACKING; BENZENE; BIOMASS